IMPLEMENTASI ASPEK GMP, SSOP, DAN SISTEM HACCP PADA UMKM ONCOM DAWUAN - Rita Purwasih (AGROINTEK, 2021)
Dawuan is a sub-district in Subang Regency, West Java, which is famous for its special food, Oncom. Oncom is one of the typical foods from Java which is a fermented product from the substrate of peanut meal or tofu pulp which has been inoculated with red oncom spore molds. The purpose of this study is to find out the description of the application of GMP, SSOP and HACCP on SMEs Oncom Dawuan, identify hazards related to the Dawuan oncom manufacturing process and provide recommendations for developing a HACCP system, to produce products that are safe for consumption. The methodology carried out in this study consisted of 4 stages: identification, data collection, data collection and processing, and literature study. The process of collecting data is obtained through surveys that are observation and interviews and the data is processed and presented using descriptive methods. The application of GMP to MSME Oncom Dawuan has serious irregularities in machinery and equipment, employees, packaging, maintenance and sanitation programs, and transportation. The aspects of SSOP have not been implemented and are not yet a concern of MSME Oncom Dawuan and the critical points that exist in raw materials and the receipt of raw materials, starters, cassava mixture, steaming, and fermentation, as well as the dangers that can contaminate products in Dawuan oncom production, include biological/microbiological, chemical and physical. Recommendations given to MSME Oncom Dawuan are related to employee hygiene, production equipment and production support, SSOP application; and the layout of the production space.